Can Instagram convince information to users? - Ilham, Romi; Siregar, Cantika Sari (Jurnal Manajemen Teknologi, 2021)
Abstract. In the age of social media, everyone can provide opinions via electronic word of mouth (eWOM). This experiment explores how users adopt culinary information on social media, especially Instagram, as one social media platform that has many users in Indonesia. With the many opinions that develop on social media, a phenomenon appears where users must sort out the information of choosing food products. The main objective of this study was to investigate the effect of source credibility and information quality on information adoption mediated attitudes towards information and information usefulness with the object of research on food products — analysis of the research model using partial least squares on 368 valid questionnaires distributed in East Java-Bali. The literature review and analytical techniques show that the source's credibility and the quality of information positively affect the adoption of information mediated attitudes towards information and the usefulness of the information. The novelty of research on the development of information adoption models is the complex source credibility variables, including expertise, trustworthiness, attractiveness, and homophily. It is an electronic persuasion that culinary business people need in the current era of social media. Keywords: E-wom, source credibility, information adoption, instagram, culinary.  Abstrak. Pada zaman media sosial, setiap orang dapat memberikan opini melalui elektronik dari mulut ke mulut (eWOM). Eksperimen ini mengeksplorasi bagaimana pengguna mengadopsi informasi kuliner pada media sosial, terutama Instagram sebagai salah satu media sosial yang memiliki banyak pengguna di Indonesia. Dengan banyaknya opini yang berkembang pada media sosial maka muncul sebuah fenomena dimana pengguna harus dapat memilah informasi dalam memilih produk makanan. Tujuan utama penelitian ini adalah untuk menyelidiki pengaruh kredibilitas sumber dan kualitas informasi terhadap adopsi informasi dimediasi sikap terhadap informasi dan kegunaan informasi dengan objek penelitian produk makanan — analisis model penelitian menggunakan parsial least square pada 368 kuesioner valid yang tersebar di jawa timur -bali. Hasil dari tinjauan literatur dan teknik analisis, bahwa kredibilitas sumber dan kualitas informasi berpengaruh positif terhadap adopsi informasi dimediasi sikap terhadap informasi dan kegunaan informasi. Kebaruan penelitian pada pengembangan model adopsi informasi dengan variabel kredibilitas sumber kompleks meliputi keahlian, kepercayaan, daya tarik, dan homofili. Hal ini merupakan persuasi elektronik yang dibutuhkan para pelaku bisnis bidang kuliner pada jaman media sosial saat ini. Kata kunci: E-wom, kredibilitas sumber, adopsi informasi, Instagram, kuliner.